Design for The Development of Tourist Attraction Facilities Timbulun Waterfall in Pesisir Selatan - Suci Rafiza Herman; Putra, Trisna (Pt. Threeple Herphi Educate, 2024)
Facilities in tourist attractions are very important to support tourist comfort, one of the tourist attractions in West Sumatera is the Timbulun waterfall. This area has great potential but the facilities are not yet developed, this is known from the absence of development documents at the Tourism and Sports Office of Pesisir Selatan Regency. For this reason, it is necessary to develop facilities for the tourist attraction of the Timbulun waterfall in Pesisir Selatan Regency, then to determine the existing facilities it is necessary to study the literature and make observations on the tourist attraction of the Timbulun waterfall. Interviews were conducted with related parties who know about the existing facilities at Timbulun waterfall. In the South Coast District. The facility development design based on the tourism development component consists of 6 A’s, namely Attraction, Amenities, Ancillary, Activities, Accessibilities and Accommodation. Furthermore, the author has verified and validated with parties who are more experts in their fields.